Acquisition of partial grain orientation information using optical microscopy. (15th January 2017) - Seita, Matteo; Nimerfroh, Michael M.; Demkowicz, Michael J.
Abstract: Optical microscopy (OM) is often the first technique used to characterize surfaces of materials because of its simplicity and low cost. However, the information obtained by OM is usually limited to the geometry and spatial distribution of microstructural features. We present an advanced OM technique to perform quantitative microstructure analysis of polycrystalline metals and to assess partial grain orientation information from measurements of reflectance over a range of incident light directions. Our technique relies on the collection of a series of optical micrographs under controlled illumination conditions. We find a marked direction-dependence of reflectance and ascribe it to sub-micron facets on the surfaces of individual grains. These surface facets are, in turn, correlated to grain orientation. We automate our technique via digital processing and numerical analysis of micrographs, enabling it to generate a wealth of microstructure data while remaining simple to use and inexpensive to implement. Graphical abstract: Image 1